The Israeli Demolition of Palestinian Houses in Jerusalem: An Overview from the Historical Perspective - Gokaru, Shuaibu Umar; Mohd Nor, Mohd Roslan; Bin Abdul Hamid, Faisal Ahmad Faisal (Jurnal Ilmiah Peuradeun, 2023)
The Israeli government has been invading and demolishing Palestinian houses in the occupied territories of Jerusalem from the outset of 1948 to date. The Israeli government’s reasons for doing so are critical to analyze, which is the article's primary purpose. This article used a descriptive approach to gather data to describe the reasons for doing such demolition. The researchers investigated, identified, and critically analyzed the frequent actions of Palestinian house demolition based on the collected data, where the qualitative method becomes the data analysis methodology. The finding reveals that, according to the Israeli government, their main reason for demolishing Palestinian houses was because they were constructed illegally without residential permits. However, the finding exposes that these claims are not justifiable; instead, the precise reason for the demolition of Palestinian houses by the Israeli government is only to evict the Palestinians from their occupied territories in Jerusalem. This also violated the position of international law and human rights, which called upon the Israeli government to allocate land to the Palestinian people. This article, therefore, recommends that more research be conducted to expose the unjustifiable actions of the Israeli government.